2019
DOI: 10.1007/978-3-030-20521-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results Using a P300 Brain-Computer Interface Speller: A Possible Interaction Effect Between Presentation Paradigm and Set of Stimuli

Abstract: Several proposals to improve the performance controlling a P300based BCI speller have been studied using the standard row-column presentation (RCP) paradigm. However, this paradigm could not be suitable for those patients with lack of gaze control. To solve that, the rapid serial visual presentation (RSVP) paradigm, which presents the stimuli located in the same position, has been proposed in previous studies. Thus, the aim of the present work is to assess if a stimuli set of pictures that improves the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Comparing the obtained results with those of previous studies that also assessed RSVP spellers using only letters as stimuli, it can be observed that the reported accuracy and ITR values of this study are similar to those reported in the literature Chennu et al, 2013;Lin et al, 2018;Won et al, 2018;Fernández-Rodríguez et al, 2019c). To the best of our knowledge, the FF condition has not been used before for communication purposes under RSVP, and the NP condition has only been evaluated in a preliminary study (Fernández-Rodríguez et al, 2019c). Thus, the performance achieved by the FF or NP paradigms cannot be fairly compared to any other study, highlighting the novelty of this work.…”
Section: Online Tasksupporting
confidence: 86%
See 3 more Smart Citations
“…Comparing the obtained results with those of previous studies that also assessed RSVP spellers using only letters as stimuli, it can be observed that the reported accuracy and ITR values of this study are similar to those reported in the literature Chennu et al, 2013;Lin et al, 2018;Won et al, 2018;Fernández-Rodríguez et al, 2019c). To the best of our knowledge, the FF condition has not been used before for communication purposes under RSVP, and the NP condition has only been evaluated in a preliminary study (Fernández-Rodríguez et al, 2019c). Thus, the performance achieved by the FF or NP paradigms cannot be fairly compared to any other study, highlighting the novelty of this work.…”
Section: Online Tasksupporting
confidence: 86%
“…Nevertheless, studies regarding the nature of the stimuli under RSVP have barely been carried out for communication purposes (i.e., RSVP spellers). In a preliminary study, neutral images and letters were compared in RSVP (Fernández-Rodríguez et al, 2019c). The results of this work showed that neutral images did not offer significant benefits as compared to letters under the RSVP paradigm.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, studies regarding the nature of the stimuli under RSVP have barely been carried out for communication purposes (i.e., RSVP spellers). In a preliminary study, neutral images and letters were compared in RSVP (Fernández-Rodríguez et al, 2019c). The results of this work showed that neutral images did not offer significant benefits as compared to letters under the RSVP paradigm.…”
Section: Introductionmentioning
confidence: 94%